2009
DOI: 10.1248/cpb.57.1227
|View full text |Cite
|
Sign up to set email alerts
|

The Constituents and Their Bioactivities of Houttuynia cordata

Abstract: Chemical investigation on the whole plant of Houttuynia cordata has resulted in the isolation of two new compounds, named as houttuynoside A (1) and houttuynamide A (2), together with thirty-eight known compounds. The structures of 1 and 2 were elucidated on the basis of spectroscopic analysis. In the inhibitory effects on herpes simplex virus type 1 (HSV-1) assay, norcepharadione B (10) showed good inhibitory activity against the replication of HSV-1. In addition, the antioxidant and antityrosinase activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…Amounts of 27.35 ± 0.35, 17.73 ± 0.40, 46.13 ± 0.26, and 77.69 ± 0.28 lg/kg of fresh weight were quantified for chlorogenic acid, caffeic acid, rutin, and quercitrin hydrate, respectively. Previous studies chemically identified bioactive components in HC extract such as quercitrin, isoquercitrin, rutin, hyperoside, chlorogenic acid, quercetin (Xu et al 2006;Chou et al 2009;Meng et al 2009;Jang et al 2011). Results from the current study showed a similar profile of bioactive components in HC extract to those from previous studies.…”
Section: Resultssupporting
confidence: 80%
“…Amounts of 27.35 ± 0.35, 17.73 ± 0.40, 46.13 ± 0.26, and 77.69 ± 0.28 lg/kg of fresh weight were quantified for chlorogenic acid, caffeic acid, rutin, and quercitrin hydrate, respectively. Previous studies chemically identified bioactive components in HC extract such as quercitrin, isoquercitrin, rutin, hyperoside, chlorogenic acid, quercetin (Xu et al 2006;Chou et al 2009;Meng et al 2009;Jang et al 2011). Results from the current study showed a similar profile of bioactive components in HC extract to those from previous studies.…”
Section: Resultssupporting
confidence: 80%
“…Some phenolic compounds in the extract of this plant have been described [15][16][17] , however, the phenolic acid composition in the commercialized fermentation products has not yet been determined. Preliminary separation and identification of individual phenolic compounds in water-soluble constituents of two commercialized fermentation products were conducted by reversed phase HPLC.…”
Section: Phenolic Acid Compositionmentioning
confidence: 99%
“…Four flavonoid compounds (rutin, hyperoside, quercitrin, and quercetin) were reported as major bioactive ingredients in H. cordata 15,16 . Two new compounds, houttuynoside A and houttuynamide A, and 38 known compounds have been also identified from a whole plant methanolic extract 17 . Nonetheless, phenolic acid composition of a plant fermentation product has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin 3-O-methyl ether and ophioglonin obtained from plants belonging to Ophioglossaceae genus have shown slight activity against HBV [50]. Since 1995 when antiviral activities against enveloped viruses were discovered in extracts of Houttuynia cordata [51], such as influenza, HIV, herpes, SARS and also in enteroviruses [51][52][53][54], 40 compounds have been isolated from the whole plant [55].…”
Section: Resultsmentioning
confidence: 99%
“…Among all of them, norcepharadione B has been identified as anti-herpes virus type 1 compound [55], quercetin may reduce virions production of HCV [56], but not against HBV [7] and quercetin 3-rhamnoside may be effective against influenza A virus [57].…”
Section: Resultsmentioning
confidence: 99%